Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Get immediate and reliable answers to your questions from a community of experienced experts on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
[tex]2x+5y= 4~~~...(i)\\\\2x-2y = 18~~~...(ii)\\\\(ii) -(i):\\\\~~~~~2x-2y -2x -5y= 18 -4\\\\\implies -7y = 14\\\\\implies y = -\dfrac{14}7\\\\\implies y= -2\\\\\text{Substitute}~ y=-2~ \text{ in eq (i):}\\\\~~~~~~2x+5(-2) = 4\\\\\implies 2x-10 = 4\\\\\implies 2x = 10+4\\\\\implies 2x =14\\\\\implies x = \dfrac{14}2\\\\\implies x =7\\\\\text{Hence}~ (x,y) =(7,-2).[/tex]
Answer:
y = -2
x = 7
Step-by-step explanation:
Solving simultaneous equation
2x + 5y = 4 ---------------(I)
2x - 2y = 18 -----------(II)
Now, multiply equation (II) by (-1) and then add the equations. So that, 'x' will be eliminated and we can find the value of 'y'
(I) 2x + 5y = 4
(II)*(-1) -2x + 2y = - 18 {Now add}
7y = -14
y = -14/7 {on dividing both sides by 7}
[tex]\sf \boxed{y= -2}[/tex]
Now plugin y = -2 in equation (I)
2x + 5*(-2) = 4
2x - 10 = 4
2x = 4 + 10 {on adding 10 to both sides}
2x = 14
x = 14/2 {Divide both sides by 2}
[tex]\sf \boxed{x = 7}[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.